Monospecific benthic δ18O data from Cape Hatteras and Blake Outer Ridge during the Mid-Holocene (2-6 ka BP) and LGM (19-23 ka BP) - Jack Wharton; Martin Renoult; Geoffrey Gebbie; Lloyd D Keigwin; Thomas M Marchitto; Mark Maslin; Delia W Oppo; David J R Thornalley (PANGAEA, 2024)
This dataset contains monospecific benthic δ18O data from cores that form depth transects at Cape Hatteras and Blake Outer Ridge. Data is from either the Mid-Holocene or LGM and is combined to form multi-species benthic δ18O means for each core during the Mid-Holocene and/or LGM (can you add a link to Vertical δ18O profiles from Cape Hatteras and Blake Outer Ridge during the Mid-Holocene (2-6 ka BP) and LGM (19-23 ka BP)?). For species that calcify in disequilibrium with the surrounding seawater, e.g., Uvigerina peregrina, species specific correction factors have been applied. For infaunal species where a range of values are published, the correction factor is determined by calculating the average offset from coeval measurements on C. wuellerstorfi or other epifaunal species, which, in all cases, are within the range of uncertainty of published correction factors. Reproducibility is the species specific error for each transect (e.g., Cape Hatteras) and timeslice (e.g., LGM) and n is the number of individual foraminifera in each measurement. Stable isotope measurements were performed using a VG Isogas SIRA mass spectrometer with Multicarb preparation system (>80 μg) and a Thermo MAT253 isotope ratio mass spectrometer with Kiel IV carbonate preparation device (<80 μg) at the Godwin Laboratory, University of Cambridge. δ18O and δ13C are reported relative to the Vienna Peedee belemnite (VPDB) standard, and for both instruments analytical precision is estimated to be better than ±0.07 extperthousand and ±0.04 extperthousand respectively.
In: Wharton, J et al. (2024): Benthic foraminiferal oxygen isotope data (δ18O) and age models from Northwest Atlantic sediment cores forming depth transects at Blake Outer Ridge and Cape Hatteras [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.967462